The Noom kitchen : 100 healthy, delicious, flexible recipes for every day - Sussman, Adeena (Simon Element, 2024)
This official Noom cookbook from the global phenomenon offers a vast array of delicious recipes that make serving health-forward foods easy for cooks of all skill levels, and provides accessible culinary guidance for those looking to kick-start their health and wellness in the kitchen.